Iridium oxide, method for producing the same, membrane electrode assembly for proton exchange membrane type water electrolyzer using the same, and proton exchange membrane type water electrolyzer
Patent Information
- Application Number
- JP2023128460
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-08-07
- Publication Date
- 2025-02-20
- Estimated Expiration
- 2043-08-07
AI Technical Summary
【0020】 本発明の酸化イリジウムは結晶子サイズと比表面積を両立することで、高い初期活性を有し、かつ、長期運転時の安定性に優れた酸化イリジウムを提供することができる。
Smart Images

Figure 2025024390000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an iridium oxide for use in proton exchange membrane type water electrolyzers, water electrolyzers, and the like. [Background technology]
[0002] In recent years, hydrogen production technology using water electrolysis has been attracting attention in response to social demands and trends against the backdrop of energy and environmental issues. For example, proton exchange membrane water electrolyzers are characterized by the use of an electrolyte layer that contains a film-like proton exchange membrane.
[0003] A proton exchange membrane water electrolyzer is generally configured by stacking multiple single electrolytic cells, each of which has a membrane electrode assembly (hereinafter referred to as "MEA") sandwiched between a pair of separators. The MEA has a structure in which an electrolyte layer is sandwiched between electrode catalyst layers in which an electrode catalyst is highly dispersed. The electrode catalyst layers are also called electrodes.
[0004] In the MEA, the following electrochemical reactions take place. First, water supplied to the anode side is oxidized by catalyst particles to produce protons, electrons, and oxygen. Next, the generated protons pass through the proton-conductive electrolyte contained in the electrode catalyst layer and the proton exchange membrane in contact with the electrode catalyst layer, and reach the cathode side electrode catalyst layer. Also, the electrons generated in the anode side electrode catalyst layer pass through the electrode catalyst layer, the porous transfer layer in contact with the side of the electrode catalyst layer different from the proton exchange membrane, the separator, and the external circuit, and reach the cathode side electrode catalyst layer. Then, the protons and electrons that reach the cathode side electrode catalyst layer react to produce hydrogen. In water electrolysis, hydrogen can be produced through the above-mentioned electrochemical reactions.
[0005] In conventional electrode catalysts, anodes use precious metal oxides such as iridium oxide, and cathodes use catalyst-supported carbon, which is a carrier made of carbon primarily composed of carbon and supports catalyst particles such as platinum or a platinum alloy.
[0006] The cost of anodes that use a large amount of iridium is an issue for proton exchange membrane water electrolyzers. Since iridium is rare and expensive, there is a demand for catalysts that are highly active and contribute to reducing the amount of iridium in the anode catalyst, and that are also stable for long-term operation, in order to expand the use of proton exchange membrane water electrolyzers.
[0007] For this reason, various research and development efforts have been made on catalysts that have high initial activity and excellent stability, and MEAs that exhibit stable electrolysis performance over a long period of time.
[0008] Prior Patent Document 1 describes amorphous iridium oxide, but from the standpoint of stability, crystalline iridium oxide is desired.
[0009] Prior Patent Document 2 describes a catalyst layer containing iridium and ruthenium, but from the viewpoint of stability during long-term operation, a catalyst layer that does not contain ruthenium is desired. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Patent No. 7297962 [Patent Document 2] Patent Publication No. 2021-045709 Summary of the Invention [Problem to be solved by the invention]
[0011] Patent Documents 1 and 2 contain amorphous iridium oxide or ruthenium, and although the initial activity is high, there are concerns about stability during long-term operation. In order to achieve improved stability during long-term operation, the catalyst needs to be composed only of iridium oxide with large crystallite size. However, iridium oxide with large crystallite size has a small specific surface area, which reduces the activity of the electrode catalyst.
[0012] An object of the present invention is to provide an iridium oxide having high initial activity and excellent stability during long-term operation. [Means for solving the problem]
[0013] The inventors neutralized an iridium-containing acidic aqueous solution with an alkaline aqueous solution and calcined the resulting iridium hydroxide, thereby obtaining an iridium hydroxide having a crystallite size of 2.0 nm or more and 4.0 nm or less as determined by X-ray diffraction and a BET specific surface area (SSA) of 70 m2 or less as determined by nitrogen adsorption measurement. 2 / g or more 120m 2 The inventors have found that it is possible to obtain iridium oxide having a high crystallite size and a high BET specific surface area (SSA) of 0.1 to 1.0 μm / g or less, and that the above-mentioned problems are solved, and have arrived at the present invention. The reason why it is possible to actually provide iridium oxide having a high crystallite size and a high BET specific surface area (SSA) is not necessarily clear, but the inventors speculate as follows. Without being bound by theory, the iridium oxide is an aggregate of highly two-dimensionally anisotropic needle-like or columnar structured particles, so that the BET specific surface area (SSA) can be maintained while improving the crystallite size. The needle-like or columnar structure of iridium oxide is thought to be formed by adding hydrochloric acid after the neutralization and then calcining.
[0014] That is, the present invention relates to iridium oxide having each of the following aspects (1) to (7), as well as a membrane electrode assembly for proton exchange membrane water electrolysis in which the iridium oxide is contained in an electrode, and a proton exchange membrane water electrolyzer.
[0015] (1) Rutile iridium oxide having a crystallite size of 2.0 nm to 4.0 nm calculated from the peak of the (110) plane of rutile iridium oxide by X-ray diffraction, and a BET specific surface area of 70 m2 measured by nitrogen adsorption measurement. 2 / g or more 120m 2 / g or less.
[0016] (2) The iridium oxide according to (1) above, characterized in that the morphology observed under an electron microscope is an aggregate of needle-like or columnar structured particles having a major axis of 200 nm or less and a minor axis of 10 nm or less, and the diameter of the aggregate is 1 μm or less.
[0017] (3) adding an oxidizing agent to the heated iridium-containing acidic aqueous solution to prepare an oxidizing agent-containing aqueous solution, and then adding an alkaline aqueous solution to the thus obtained aqueous solution to neutralize it, thereby causing the precipitation of iridium hydroxide; The aqueous solution containing the precipitate is filtered and the remaining precipitate is washed to obtain a filter cake of iridium hydroxide; 3. The method for producing iridium oxide according to claim 1 or 2, characterized in that the solvent is distilled off from an iridium hydroxide suspension obtained by adding hydrochloric acid to the filter cake, and the dried product obtained by distilling off the solvent is calcined at 420 to 470° C. in an oxygen-containing atmosphere.
[0018] (4) A membrane electrode assembly for proton exchange membrane water electrolysis, comprising an electrode containing the iridium oxide according to (1) or (2).
[0019] (5) A proton exchange membrane water electrolysis cell, comprising the iridium oxide according to (1) or (2) contained in an electrode of a membrane electrode assembly. Effect of the Invention
[0020] The iridium oxide of the present invention satisfies both the crystallite size and the specific surface area, and thus it is possible to provide iridium oxide that has high initial activity and excellent stability during long-term operation. [Brief description of the drawings]
[0021] [Figure 1] FIG. 1 is a diagram showing the relationship between the crystallite size and the specific surface area of iridium oxide obtained in the examples and comparative examples. [Diagram 2] FIG. 1 shows the morphology of iridium oxide obtained in the examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0022] Next, the present invention will be described based on an embodiment, however, the present invention is not limited to the embodiment described below.
[0023] In the present invention, the crystallite size of iridium oxide measured by X-ray diffraction is 2.0 nm to 4.0 nm, and the BET specific surface area (SSA) measured by nitrogen adsorption is 70 m 2 / g or more 120m 2 / g or less. Figure 1 shows the relationship between the crystallite size and BET specific surface area (SSA) of iridium oxide in the present invention and the prior art. The iridium oxide in the present invention is an iridium oxide that achieves a high balance between crystallite size and BET specific surface area (SSA) compared to the prior art.
[0024] The iridium oxide may contain, for example, platinum, rhodium, etc., as long as the object of the present invention is achieved.
[0025] The method for producing iridium oxide according to the embodiment described in (3) above can be more specifically described as follows.
[0026] Examples of iridium-containing acidic aqueous solutions include aqueous hydrochloric acid or nitric acid solutions of iridium chloride (III), iridium chloride (IV), chloroiridic acid (IV), ammonium chloroiridic acid (IV), iridium nitrate (IV), and iridium acetate (III).
[0027] First, an oxidizing agent is added to a heated iridium-containing acidic aqueous solution, and then an alkaline aqueous solution is added to neutralize the solution, causing the precipitation of iridium hydroxide.
[0028] The heating temperature can be 80°C to 100°C. As the oxidizing agent, sodium bromate, potassium bromate, chlorine gas, and hydrogen peroxide can be used. As the alkaline aqueous solution, an aqueous sodium hydroxide solution, an aqueous potassium hydroxide solution, and an aqueous sodium carbonate solution can be used. The pH at the time of neutralization can be 10 to 12.
[0029] Next, the neutralized aqueous solution containing the iridium hydroxide precipitate was filtered and washed to obtain a filter cake.
[0030] Next, hydrochloric acid was added to the filter cake to adjust the pH to 0 to 2 to obtain an iridium hydroxide suspension, and the solvent was distilled off from the suspension at 40 to 60°C using an evaporator, and the dried product after the treatment was crushed to obtain a powder.
[0031] Next, the powder is calcined in an oxygen-containing atmosphere, for example, in air, at 420 to 470° C. for 3 to 7 hours to obtain iridium oxide powder having a needle-like or columnar structure. For calcination, an electric furnace can be used, for example.
[0032] The obtained iridium oxide is an aggregate of highly two-dimensionally anisotropic needle-like or columnar structure particles, and therefore the BET specific surface area (SSA) can be maintained while improving the crystallite size. The needle-like or columnar structure of iridium oxide is believed to be formed by adding hydrochloric acid after the neutralization and then calcining.
[0033] By increasing the crystallite size of iridium oxide to 2.0 nm or more, deterioration of iridium oxide can be suppressed, enabling it to exhibit high stability.
[0034] Corrosion and loss of iridium oxide in an electrode catalyst is likely to occur starting from defective sites on the iridium oxide surface, and therefore it is preferable to reduce defects on the iridium oxide surface by increasing the crystallinity of the iridium oxide.
[0035] On the other hand, if the crystallite size exceeds 4.0 nm, the BET specific surface area (SSA) described below decreases, making it impossible to achieve a high level of both the BET specific surface area (SSA) and the crystallite size.
[0036] The crystallite size is preferably 2.1 nm or more and 3.9 nm or less, and more preferably 2.3 nm or more and 3.8 nm or less.
[0037] The BET specific surface area (SSA) is 70 m 2 By increasing the BET specific surface area (SSA) to 1 / g or more, it becomes possible to exhibit high initial activity. The BET specific surface area (SSA) represents the area that becomes the active site for the oxygen generating reaction, and the higher the BET specific surface area (SSA), the higher the initial activity.
[0038] In general, in iridium oxide for proton exchange membrane water electrolysis, by increasing the BET specific surface area (SSA), sufficient active sites for the oxygen evolution reaction can be secured, enabling the material to exhibit high initial activity.
[0039] Corrosion and loss of the electrode catalyst are particularly likely to occur at defective sites such as steps and kinks, and therefore iridium oxide with a large specific surface area and small crystallite size may be less stable. Therefore, in order to achieve both initial activity and stability, it is desirable to limit the BET specific surface area (SSA) to an appropriate value. That is, the BET specific surface area (SSA) should be set to 120 m 2 By keeping the BET specific surface area (SSA) at 120 m or less, the stability of iridium oxide can be suppressed from decreasing. 2 If the molecular weight is increased to more than 1 / g, the crystallite size described above decreases, and it becomes impossible to achieve both the crystallite size and the BET specific surface area (SSA).
[0040] The BET specific surface area (SSA) is preferably 75m 2 / g or more, more preferably 80m 2 / g or more 115m 2 / g or less.
[0041] In order to achieve both a large crystallite size and a large BET specific surface area (SSA), the morphology observed by electron microscope is preferably an aggregate of needle-like or columnar particles with a major axis of 200 nm or less and a minor axis of 10 nm or less.
[0042] The aggregates preferably have a diameter of 1 μm or less in order to reduce the material transport resistance and electron transfer resistance in the catalyst layer and to prevent perforation of the electrolyte membrane.
[0043] The iridium oxide of the present invention must have a crystallite size of 2.0 nm to 4.0 nm, and must have needle-like or columnar structure particles with a major axis of 200 nm or less and a minor axis of 10 nm or less. By setting the crystallite size of iridium oxide within the above range and having the above structure, it is possible to improve the BET specific surface area (SSA) while increasing the crystallinity, and to exhibit high initial activity.
[0044] The BET specific surface area (SSA) of the iridium oxide of the present invention is calculated by analyzing the nitrogen gas adsorption isotherm using the BJH method. 2 / g or more 120m 2 A BET specific surface area (SSA) of less than or equal to 1 / g is important.
[0045] BET specific surface area (SSA) is 70m 2 If the BET specific surface area (SSA) is less than 120 m 2 If it is greater than / g, the number of defects such as steps and kinks increases, leading to a decrease in stability.
[0046] The crystallite size of the iridium oxide of the present invention is calculated from the (110) plane of rutile iridium oxide (IrO2). The crystallite size of the (110) plane of iridium oxide can be in the range of 2.0 nm to 4.0 nm.
[0047] The crystallite size of the (110) face of iridium oxide is within the above range, and both initial activity and stability can be achieved. When the crystallite size of the (110) face of iridium oxide is less than 2.0 nm, the initial activity can be improved due to the high BET specific surface area (SSA) of iridium oxide, but the stability decreases due to an increase in defective sites that are the starting points for corrosion loss. When the crystallite size of the (110) face of iridium oxide is more than 4.0 nm, the stability can be improved due to a decrease in defective sites, but the active sites required for the oxygen generation reaction are insufficient due to the low BET specific surface area (SSA) of iridium oxide, leading to a decrease in initial activity.
[0048] The iridium oxide of the present invention is composed of single-phase rutile-structure iridium oxide. EXAMPLES
[0049] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to these examples.
[0050] Example 1 16L of an aqueous solution of iridium chloride hydrochloride with a pH of 1.0 or less containing 850g of iridium was heated to 95°C, 10.7g of sodium bromate was added, and immediately 40% aqueous sodium hydroxide was added to neutralize the solution to pH 11.0, thereby obtaining a precipitate of iridium hydroxide. The precipitate of iridium hydroxide was cooled to room temperature and filtered and washed to obtain a filter cake. Hydrochloric acid was added to the obtained filter cake to adjust the pH to 1.0. The solvent was removed by distillation at 50°C under reduced pressure using an evaporator, and the mixture was crushed to obtain a powder, which was then calcined in an electric furnace in the air at 430°C for 5 hours to obtain an iridium oxide powder with a needle-like or columnar structure.
[0051] Example 2 Example 2 was prepared in the same manner as in Example 1, except that the temperature during distillation of the solvent using an evaporator was 60° C., to obtain an iridium oxide powder having a needle-like or columnar structure.
[0052] Example 3 The same procedure as in Example 1 was carried out except that the supernatant was removed using a centrifuge and then the solvent was distilled off, to obtain an iridium oxide powder having a needle-like or columnar structure of Example 3. Comparative Example
[0053] Comparative Example 1 Commercially available iridium oxide (Premion® from Alfa Aesar) that does not have an acicular or columnar structure was used.
[0054] Comparative Example 2 An iridium oxide powder of Comparative Example 2 was obtained in the same manner as in Example 1, except that the firing was carried out at 550° C. for 5 hours.
[0055] Comparative Example 3 0.4 L of an iridium chloride hydrochloride acid solution containing 22 g of iridium and having a pH of 1.0 or less was heated to 95°C, 0.33 g of potassium bromate was added, and a potassium hydroxide solution was added to neutralize the pH to 11.1, thereby obtaining a precipitate of iridium hydroxide. After neutralization, the mixture was heated and stirred for 1 hour, filtered, washed, dried, and crushed into powder, and then calcined in an electric furnace in the air at 500°C for 5 hours to obtain an iridium oxide powder of Comparative Example 3.
[0056] The following physical property evaluations were carried out for each of the iridium oxides in the Examples and Comparative Examples. The results are shown in Table 1.
[0057] [Measurement of BET specific surface area of iridium oxide] The specific surface area of iridium oxide was measured by the BET flow method using a fully automatic specific surface area measuring device (Macsorb (registered trademark) HM model-1220 manufactured by Mountec). The pretreatment conditions were a degassing temperature of 100° C. and a degassing time of 20 minutes.
[0058] [Measurement of crystallite size of iridium oxide] The crystallite size of iridium oxide was measured using an X-ray diffractometer (Rigaku SmartLab) with CuKα radiation as the radiation source under the following measurement conditions to obtain an XRD pattern of the catalyst-supported carbon. The obtained XRD pattern was analyzed using integrated powder X-ray analysis software (Rigaku PDXL), and the crystallite size was determined from the peak of the rutile structure iridium oxide (110) plane at around 28°.
[0059] XRD measurement conditions Line source: CuKα (line focus), wavelength: 1.541836Å Operation axis: 2θ / θ, Measurement method: Continuous, Count unit: cps Start angle: 10.0°, end angle: 90.0°, number of times accumulated: 1 Sampling width: 0.01°, Scan speed: 4° / min Voltage: 40kV, Current: 30mA Incident parallel slit: Solar 5.0°, length limiting slit: 10mm Receiving parallel slit: Solar 5.0°, Receiving slit: 20mm Offset angle: 0° Goniometer radius: 300mm, Optical system: Concentration method Slit: D / teX Ultra slit Detector: D / teX Ultra 250 Ni-Kβ filter: None
[0060] [Morphological observation of iridium oxide] The morphology of iridium oxide was observed using an atomic resolution analytical electron microscope (JEM-ARM200F, JEOL, accelerating voltage 200 kV).
[0061] [Table 1]
[0062] In Examples 1 to 3, all of the iridium oxides had a BET specific surface area of 70 m 2 / g or more 120m 2 The iridium oxide thus obtained had a specific surface area of 0.1 μm / g or less and a crystallite size of 2.0 nm to 4.0 nm, and exhibited both a high specific surface area and high crystallinity. The morphology of the iridium oxide was an aggregate of particles with a needle-like or columnar structure.
[0063] In Comparative Example 1, the BET specific surface area of iridium oxide is 70 m 2 / g or less. Since no peak was observed on the (110) plane of rutile iridium oxide, the crystallite size could not be calculated, and thus amorphous iridium oxide was obtained.
[0064] In Comparative Examples 2 and 3, the BET specific surface area of the iridium oxide was as low as 70 m2 / g or less, and the crystallite size was as high as 4.0 nm or more, so that the iridium oxide obtained was highly crystallized. Note that the morphology of Comparative Example 2 was an aggregate of particles with a needle-like or columnar structure.
[0065] In order to evaluate the performance as a catalyst for proton exchange membrane water electrolysis, the iridium oxides of the examples and comparative examples were evaluated by the following method.
[0066] 1. Electrode Preparation 6.3 mg (as Ir) of iridium oxide of each Example and Comparative Example, 8.0 mL of pure water, 17.4 μL of ionomer (Nafion DE520CS manufactured by Chemours), and 8.0 mL of ethanol (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) were mixed and dispersed for 30 hours using an ultrasonic disperser to prepare a catalyst ink. The catalyst ink was applied to a gold disk (diameter 5 mm) so that the amount of iridium was 30 μg / cm2, and a measurement electrode was prepared.
[0067] 2. Electrochemical Measurements The measurement electrode was immersed in 0.1 mol / L perchloric acid at 23°C saturated with nitrogen gas, and a reversible hydrogen electrode (RHE) was used as the reference electrode and a platinum wire was used as the counter electrode. Cyclic voltammetry was performed for 100 cycles at a potential scanning range of 0.05 to 1.20 V (vs. RHE) and a potential scanning rate of 50 mV / sec using a potentiogalvanostat (HZ-7000 manufactured by Hokuto Denko). Then, a polarization curve was measured at a potential of 1.00 V to 1.55 V (vs. RHE) and a potential scanning rate of 1 mV / sec using a rotating electrode device (HR-500 manufactured by Hokuto Denko) while rotating the measurement electrode at 2500 rpm. The mass activity was calculated from the obtained polarization curve by dividing the current value at 1.50 V (vs. RHE) by the amount of iridium on the electrode. The measurement of the polarization curve was repeated four times, and the mass activity obtained from the fourth polarization curve (mass activity after electrolysis test) was divided by the first polarization curve (initial activity) to calculate the activity retention rate.
[0068] [Table 2]
[0069] In Examples 1 to 3, the crystallite size is 2.0 nm or more and 4.0 nm or less, and the BET specific surface area (SSA) measured by nitrogen adsorption is 70 m 2 / g or more 120m 2 / g or less, achieving a high level of balance between crystallite size and BET specific surface area, it has been possible to obtain iridium oxide with high initial activity of 20 A / g or more, while improving the activity retention rate by 5% or more compared to conventional technologies and providing excellent stability.
[0070] In Comparative Example 1, the BET specific surface area (SSA) measured by nitrogen adsorption was 70 m 2 / g or less, and the crystallite size was small at 2.0 nm or less, so the mass activity was low at 20 A / g or less, and the activity retention rate was 91.5%, resulting in iridium oxide with low initial activity and stability.
[0071] In Comparative Examples 2 and 3, the crystallite size was as large as 2.0 nm or more, while the BET specific surface area (SSA) measured by nitrogen adsorption was 70 m 2 The iridium oxide thus obtained had a low initial activity of less than 20 A / g and a low mass activity of less than 20 A / g. [Industrial Applicability]
[0072] The iridium oxide according to the present disclosure has high initial activity and excellent stability, and can therefore be used as an electrode catalyst in a membrane electrode assembly for proton exchange membrane water electrolysis.
Claims
1. The iridium oxide has a rutile structure, and the crystallite size calculated from the peak of the (110) plane of the rutile iridium oxide by X-ray diffraction is 2.0 nm to 4.0 nm, and the BET specific surface area measured by nitrogen adsorption measurement is 70 m 2 / g or more 120m 2 / g or less.
2. 2. The iridium oxide according to claim 1, characterized in that the morphology observed by electron microscope is an aggregate of needle-like or columnar structured particles with a major axis of 200 nm or less and a minor axis of 10 nm or less, and the diameter of the aggregate is 1 μm or less.
3. An oxidizing agent is added to the heated iridium-containing acidic aqueous solution to prepare an oxidizing agent-containing aqueous solution, and an alkaline aqueous solution is added to the thus obtained aqueous solution to neutralize it, thereby causing precipitation of iridium hydroxide; The aqueous solution containing the precipitate is filtered and the remaining precipitate is washed to obtain a filter cake of iridium hydroxide; The method for producing iridium oxide according to claim 1 or 2, characterized in that the solvent is distilled off from an iridium hydroxide suspension obtained by adding hydrochloric acid to the filter cake, and the dried product obtained by distilling off the solvent is calcined at 420 to 470° C. in an oxygen-containing atmosphere.
4. 3. A membrane electrode assembly for proton exchange membrane water electrolysis, comprising an electrode containing the iridium oxide according to claim 1 or 2.
5. 3. A proton exchange membrane water electrolysis cell comprising the iridium oxide according to claim 1 or 2 contained in an electrode of a membrane electrode assembly.
Citation Information
Patent Citations
A porous IrO2 oxygen evolution catalyst with ultra-high specific surface area and its preparation method
CN106111130B
Preparation method of PEM water electrolysis oxygen evolution catalyst iridium oxide
CN114477320A
Process for preparing nano iridium dioxide through strong dispersion
CN115465904A
A method for manufacturing a mixed filter using an embed charcoal filter and the manufactured mixed filter
KR1020200100485A
Retainer Ring in Chemical Mechanical Polishing Machine And Manufacturing Methods Thereof
KR1020250009851A